Primary and secondary functions of HLA-E are determined by stability and conformation of the peptide-bound complexes - Walters, LC; Rozbesky, D; Harlos, K; Quastel, M; Sun, H; Springer, S; Rambo, RP; Mohammed, F; Jones, EY; McMichael, AJ; Gillespie, GM (Cell Press, 2022)
MHC-E regulates NK cells by displaying MHC class Ia signal peptides (VL9) to NKG2A:CD94 receptors. MHC-E can also present sequence-diverse, lower-affinity, pathogen-derived peptides to T cell receptors (TCRs) on CD8+ T cells. To understand these affinity differences, human MHC-E (HLA-E)-VL9 versus pathogen-derived peptide structures are compared. Small-angle X-ray scatter (SAXS) measures biophysical parameters in solution, allowing comparison with crystal structures. For HLA-E-VL9, there is concordance between SAXS and crystal parameters. In contrast, HLA-E-bound pathogen-derived peptides produce larger SAXS dimensions that reduce to their crystallographic dimensions only when excess peptide is supplied. Further crystallographic analysis demonstrates three amino acids, exclusive to MHC-E, that not only position VL9 close to the α2 helix, but also allow non-VL9 peptide binding with re-configuration of a key TCR-interacting α2 region. Thus, non-VL9-bound peptides introduce an alternative peptide-binding motif and surface recognition landscape, providing a likely basis for VL9- and non-VL9-HLA-E immune discrimination